Pengaruh E-WOM, Harga Tiket dan Preferensi Wisatawan Terhadap Minat Berkunjung Wisatawan Pada Pantai Mangrove - Collyn, Daniel; Zalukhu, Rika Surianto (Accounting Progress, 2024)
This study aims to determine the influence of E-WOM, ticket prices, and tourist preferences on tourists' intention to visit Mangrove Beach, both partially and simultaneously. The research employs a quantitative method, examining variables such as visiting intention as the dependent variable and E-WOM, ticket prices, and tourist preferences as independent variables. The study targeted individuals aged 17 and above who have heard about Mangrove Beach but have never visited the site. A total of 96 respondents were sampled using a simple random sampling technique. Primary data were collected through questionnaires, with respondents' perceptions measured using a Likert scale. The data were analyzed using multiple linear regression analysis. The results indicate that E-WOM and ticket prices partially have a positive and significant effect on tourists' intention to visit Mangrove Beach. Tourist preferences, however, partially have a positive but insignificant effect on visiting intention. Furthermore, E-WOM, ticket prices, and tourist preferences simultaneously have a significant influence on visiting intention. The direct implication of this study is that Mangrove Beach managers should leverage digital media to enhance E-WOM, such as encouraging positive reviews on online platforms, as E-WOM significantly influences visiting intention.